2015
DOI: 10.1016/j.copsyc.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Trust promotes unethical behavior: excessive trust, opportunistic exploitation, and strategic exploitation

Abstract: Trust is critical for our cooperation and effective working relationships, but trust also enables exploitation and unethical behavior. Prior trust research has disproportionately focused on the benefits of trust, even though some of the most egregious unethical behaviors occur because of misplaced trust. Targets of exploitation misplace their trust, because they rely on the wrong cues and are exploited by people who either opportunistically or strategically take advantage of their trust. We call for future wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Overall, the dark side of trust in management literature has been found to have negative consequences for individuals and organizations such as allowing unethical behavior [50], overreliance on automation [27], poor judgment [13], management complacency [26], and underperformance [32]. In light of this understanding in management literature, little attention has been paid to the dark side of trust in ISec and IS research.…”
Section: Dark Side Trust In Cybersecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the dark side of trust in management literature has been found to have negative consequences for individuals and organizations such as allowing unethical behavior [50], overreliance on automation [27], poor judgment [13], management complacency [26], and underperformance [32]. In light of this understanding in management literature, little attention has been paid to the dark side of trust in ISec and IS research.…”
Section: Dark Side Trust In Cybersecuritymentioning
confidence: 99%
“…Trust in information systems (IS) research has largely been shown to be positive in different contexts such as electronic markets [2], e-commerce [40], website design [9], and online social networks [3]. Trust though has also been conceptualized and shown to result in negative consequences [12,34,37,50] as individuals may maintain trust unconditionally and over and above evidence to the contrary [12]. Trust, therefore, has been shown to have a "bright" and "dark" side stimulating both positive and negative consequences for individuals and organizations.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, negotiators who confront angry counterparts may also experience feelings of anger, and these feelings may make them more likely to use deception for many reasons. First, anger makes people focused on retaliation (Allred, ; Frank, ; Pillutla & Murnighan, ), and the desire to retaliate increases the perceived benefits and reduces the perceived costs of deception (Yip & Schweitzer, ). Second, anger makes negotiators more competitive (Forgas, ; Pillutla & Murnighan, ), and competitive negotiators are more likely to use deception than cooperative negotiators (Schweitzer, DeChurch, & Gibson, ).…”
Section: The Interpersonal Emotion Deception Model (Iedm)mentioning
confidence: 99%
“…In recent years, scholars have investigated the relationship between trust and unethical decision making (Jiang et al, ; Matherne & Litchfield, ; Yip & Schweitzer, ). Gargiulo and Ertug () indicated that trust can have negative effects, such as inducing blind faith.…”
Section: Introductionmentioning
confidence: 99%
“…Gargiulo and Ertug () indicated that trust can have negative effects, such as inducing blind faith. Yip and Schweitzer () argued that exploitation, such as Ponzi schemes or consumer fraud, normally involves trust. In other situations, a trust relationship can cause one party to accept less‐than‐satisfactory outcomes.…”
Section: Introductionmentioning
confidence: 99%